Robot rebellion - Neal, Rie; Shipman, Talitha (2023)
"When Astrid and the rest of the Shooting Stars find out that their teacher, Ms. Ruiz, is about to celebrate a big birthday, they band together to create the perfect gift. Her big day happens to be the same as the upcoming robotics competition and they decide to do something there. With the help of Astrid's big sister, Stella, they program their robot to do a fun dance and give Ms. Ruiz a sweet surprise. But on the day of the competition, the data for the Shooting Stars robot somehow gets mixed up with another one! Will their fun present end up being a major malfunction?"--
v. 4. Robot rebellion
Ages 6 to 9